2022
DOI: 10.3389/fbioe.2022.943712
|View full text |Cite
|
Sign up to set email alerts
|

Tracking tools of extracellular vesicles for biomedical research

Abstract: Imaging of extracellular vesicles (EVs) will facilitate a better understanding of their biological functions and their potential as therapeutics and drug delivery vehicles. In order to clarify EV-mediated cellular communication in vitro and to track the bio-distribution of EV in vivo, various strategies have been developed to label and image EVs. In this review, we summarized recent advances in the tracking of EVs, demonstrating the methods for labeling and imaging of EVs, in which the labeling methods include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 104 publications
0
14
0
Order By: Relevance
“…Even specific exosomes hide numerous problems due to the wrapping of various complex molecules, including the uncontrollability of the effects produced by unknown molecules and the quantification of miRNA, lncRNA, and circRNA in MSC-Exos [ 168 ]. In addition, there is still a lack of pharmacokinetics and biodistribution of exosomes in vivo [ 169 , 170 ]. Undeniably, several organizations, including the International Society for Extracellular Vesicles, are try to develop guidelines for MSC-Exos for the treatment of OA [ 171 ].…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…Even specific exosomes hide numerous problems due to the wrapping of various complex molecules, including the uncontrollability of the effects produced by unknown molecules and the quantification of miRNA, lncRNA, and circRNA in MSC-Exos [ 168 ]. In addition, there is still a lack of pharmacokinetics and biodistribution of exosomes in vivo [ 169 , 170 ]. Undeniably, several organizations, including the International Society for Extracellular Vesicles, are try to develop guidelines for MSC-Exos for the treatment of OA [ 171 ].…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…One possibility is to use naturally derived particles with lipid membranes to deliver therapeutics across the BBB. Extracellular vesicles (EVs) are small particles naturally released from cells that carry and deliver bioactive molecules as a method of cell-to-cell communication, and EVs from various types of cells have been shown to target tumors and cross the BBB 12,13 . EVs can be classified by mechanism of biogenesis, size, function, or composition; examples of EVs classified by biogenesis include exosomes, microvesicles, and apoptotic bodies 14 .…”
Section: Introductionmentioning
confidence: 99%
“…20 Several research groups have investigated the feasibility of using EV to transport pharmaceuticals, nucleic acids, and proteins for therapeutic purposes. 21,22 In this study, we identified potential candidate genes using an in vivo genetic loss-of-function screening approach based on CRISPR-Cas9 genome editing to identify genes that increase the sensitivity or cause radioresistance in an orthotopic GBM model. Ferroptosis, triggered by the enzyme glutathione synthetase (GSS), has been shown to be a determinant in radiosensitization.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, EV proteins include CD47, a transmembrane protein linked with integrins that helps shield cells from phagocytosis . Several research groups have investigated the feasibility of using EV to transport pharmaceuticals, nucleic acids, and proteins for therapeutic purposes. , …”
Section: Introductionmentioning
confidence: 99%